Chlorohydrination of allyl chloride with HCl and H2O2 catalyzed by hollow titanium silicate zeolite to produce dichloropropanol. Issue 5 (6th January 2017) - Peng, Xinxin; Xia, Changjiu; Lin, Min; Yuan, Hui; Zhu, Bin; Zhang, Yao; Wang, Baorong; Shu, Xingtian
Abstract : A novel chlorohydrination process of allyl chloride with HCl and H2 O2 catalyzed by hollow titanium silicate zeolite has been developed, overcoming the significant drawbacks of traditional Cl2 -based route. Abstract : Overall, over 95% of epichlorohydrin is industrially manufactured via the chlorohydrination route with hazardous Cl2 as a reagent, which brings serious operation and pollution problems. Herein, we describe a novel Cl2 -free process for the synthesis of dichloropropanols from allyl chloride with H2 O2 and HCl catalyzed by hollow titanium silicate zeolite under mild conditions. A high conversion and overall dichloropropanol selectivity exceeding 95% are simultaneously achieved, and the heterogeneous catalyst is highly stable and amenable for reuse. Comprehensive experimental and spectroscopic data suggest that the Lewis acidity of the framework Ti species has a synergistic effect with the Brønsted acidity of HCl that promotes the epoxidation of allyl chloride and the ring opening of the epoxy groups.